(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The extent of therapeutic advantages led to the development of controlled drug delivery systems, which could be taken once a day. The prime objective of these dosage forms would be single dose, which releases the active ingredient over an extended period. Secondly, it should release the active entity directly to the site of action, thus, minimizing or eliminating side effects. In the present manuscript, fexofenadine was selected as drug of choice to design effervescent gastric floating matrix tablets (EGFMT) using natural polymers as well as synthetic polymers as matrix-forming agents. Natural polymers comprise bhara gum, grewia gum and mucuna gum, whereas synthetic polymers consist of hydroxypropyl methylcellulose (HPMC) K4M, K15M, and K100M. These were compared; it was found that low concentrations of natural gum were enough to produce prolonged release. Hence out of three natural gums that were available, bhara gum had given promising results. Therefore bhara gum was selected for further studies.